Transposition of SRY into the ancestral pseudoautosomal region creates a new pseudoautosomal boundary in a progenitor of simian primates - Gläser, Birgitta; Myrtek, Daniel; Rumpler, Yves; Schiebel, Katrin; Hauwy, Marcel; Rappold, Gudrun; Schempp, Werner (Human molecular genetics, 1999)
We have isolated the prosimian lemur homologues for STS and SRY. FISH unambiguously co-localized STS with SHOX, IL3RA, ANT3 and PRK into the meiotic X-Y pairing region (PAR) of lemurs. In contrast to the close proximity of SRY to the pseudoautosomal boundary (PAB) on the Y chromosome in simian primates, SRY maps distant from the PAR in lemurs. Most interestingly, we were able to determine a DNA sequence divergence of 12.5% between the human and lemur SRY HMG box. This divergence directs to a 52 million year period of separate evolution of human and lemur SRY genes. Phylogenetically, this time period falls in between the times that prosimians and New World monkeys branched from the human lineage. Thus, we conclude that ∼52 million years ago a transposition of SRY into the ancestral eutherian PAR distal to STS and PRK defined a new PAB in a simian progenitor. By this event, STSand PRK, amongst other genes, were excluded from the X-Y crossover process and thus became susceptible to rearrangements and/or deterioration on the Y chromosome in simian primates.
Gesehen am 06.04.2021